Philosophical Progress : And Other Philosophical Studies. - Rescher, Nicholas (De Gruyter, 2014)
The nine original essays collected in this volume explore the themes of philosophical progress, ultimate explanation, the metaphysics of free will, and the relation of sciences and religion. These essays exemplify Nicholas Rescher''s characteristic mode of combining historical perspectives with analytical elucidation on philosophically contested issues and utilize this methodology to address some of the salient problems of the field.